Evaluation of serum prolidase activity in patients with slow coronary flow - Suner, Arif; Nurdag, Abdullah; Polat, Mustafa; Kaya, Hakan; Koroglu, Sedat; Acar, Gurkan; Sezen, Hatice (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Slow coronary flow (SCF) is described as the slow passage of contrast to distal coronaries despite anatomically normal coronary arteries. It has been shown that increased serum prolidase activity (SPA) correlates with collagen turnover. Increased collagen turnover might be associated with the development of atherosclerotic plaques. Aim : To investigate the relationship between serum prolidase activity and slow coronary flow. Material and methods : This cross-sectional study included 40 SCF patients (mean age: 55.0 ±9.5 years, 20 females) and 40 controls (mean age: 53.9 ±8.2 years, 21 females) with normal coronary anatomy and normal coronary flow. The Thrombolysis in Myocardial Infarction (TIMI) frame-count (TFC) method was used for SCF diagnosis. Serum prolidase activity was measured spectrophotometrically, and the relevant parameters were compared between the groups. Results : There were no statistically significant differences between the SCF and control groups in terms of basic demographic, clinical, and laboratory data. However, the SPA was significantly higher in the SCF group compared to the control (702.7 ±13.8 and 683.9 ±13.2 respectively, p < 0.001). Serum prolidase activity was significantly correlated with the mean TFC (r = 0.463, p < 0.001). The overall findings of this study support the predictive accuracy of the serum prolidase activity in our cohort, with a statistically significant ROC value of 681.3. Conclusions : Our study showed that SPA was increased in SCF patients. The activity of this enzyme was significantly correlated with the mean TFC.